Telaah Fikih dan Perundang-undangan di Indonesia tentang Monogami dalam Perjanjian Perkawinan - Subhan, Moh (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2025)
Abstract The focus of the study in this article is monogamy as a clause in a marriage agreement from the perspective of Islamic jurisprudence and legislation in Indonesia. Legal norms are used as the discussion method. The data sources used are secondary data taken from the Qur'an, hadith, Islamic jurisprudence, and legislation in Indonesia; Civil Code, Marriage Law Number 16 of 2016 and the Compilation of Islamic Law. The data analysis method uses qualitative descriptive analysis. The results of the study state that monogamy as one of the clauses of a marriage agreement from the perspective of Islamic jurisprudence is still debatable, while from the perspective of legislation in Indonesia; Civil Code, Marriage Law and the Compilation of Islamic Law, such an agreement is permitted as long as it does not conflict with moral norms, laws and public order